Gender Inequality in Indonesia: Facts and Legal Analysis - Larasati, Novia Puspa Ayu (Law Research Review Quarterly, 2021)
the present time, the law is still considered discriminatory and not gender-just. Whereas the law should not regard gender to guarantee the fulfillment of women's rights. Women's rights are still not protected. Equality and elimination of discrimination against women are often the center of attention and a shared commitment to implement them. However, in social life, the achievement of equality of women's dignity still has not shown significant progress. So, if there is discrimination against women, it is a violation of women's rights. Women's rights violations occur because of many things, including the result of the legal system, where women become victims of the system. Many women's rights to work still have a lot of conflict about the role of women in the public sector. Today, discrimination against women is still very visible in the world of work. There are so many women who do not get the right to work. This research found that the structure of the company, rarely do we see women who get a place as a leader, in addition to the acceptance of female workers companies put many terms, such as looking attractive, not married, must stay in dormitory and so forth. Their salaries are sometimes different from male workers. Like male workers, women workers also have equal opportunities in the world of work. While there are many legislations governing the rights of women workers, it seems that many companies deliberately do not socialize it and even ignore the legislation just like that.